(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The article analyzes the periodicals of the Black Sea province at the turn of the XIX-XX centuries, it considers the features of the editorial policy of the newspaper «North Caucasus» in highlighting the daily life of the Black Sea province. Key words: Black Sea province, periodicals, F.S. Leontovich, Novorossiysk leaflet, Black Sea coast, North Caucasus, editorial policy, everyday life. DOI 10.18522/1995-0640-2020-1-227-232